Effect of Flyers on Knowledge and Adherence to Medication of Hypertensive Patients - Husnawati; Reni Zulfitri; Fina Aryani; Septi Muharni; Fitra Ramadhan (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Knowledge and adherence to taking medication in patients with hypertension is very important because knowing and adhering in taking antihypertensive drugs can control the blood pressure of people with hypertension. The purpose of this study was to determine the effect of giving flyers on knowledge and adherence to taking medication for hypertensive patients. The method used in this research is a quasi-experimental method, with a non-randomized control group pretest and posttest design which was carried out on 96 respondents with purposive sampling technique. Collecting data for knowledge using the knowledge questionnaire, and adherence using the MMAS-8 scale. Data were analyzed using Wilcoxon test and Mann-Whitney test. The results of the study on hypertensive patients showed that giving flyers had a significant effect on knowledge with a p value = 0.000 and on patient adherence with a p value = 0.000.